1994
DOI: 10.1128/aac.38.5.1041
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of ermQ, the predominant macrolide-lincosamide-streptogramin B resistance gene in Clostridium perfringens

Abstract: The erythromycin resistance determinant from Clostridium perfringens JIR100 has been cloned, sequenced, and shown to be expressed in Escherichia coli. An open reading frame with sequence similarity to erm genes from other bacteria was identified and designated the ermQ gene. On the basis of comparative sequence analysis, it was concluded that the ermQ gene represented a new Erm hybridization class, designated ErmQ. Genes belonging to the ErmQ class were found to be widespread in C. perfringens, since 30 of 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
0
25
2
Order By: Relevance
“…None of the strains contained the ermF gene or the ermQ gene, which has been found primarily in Clostridium perfringens (3). Examples of tet genes were also found in strains other than those shown in Table 1.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…None of the strains contained the ermF gene or the ermQ gene, which has been found primarily in Clostridium perfringens (3). Examples of tet genes were also found in strains other than those shown in Table 1.…”
mentioning
confidence: 91%
“…Whereas ermF and tetQ are prevalent in Bacteroides and related genera, ermA, ermB, and tetM have been found in a variety of gram-positive bacteria as well as in some gramnegative bacteria (1, 2, 13). The ermQ and ermT genes have been found primarily in gram-positive bacteria (3,19). As shown in Table 1, the ermA and ermC genes were found in some of the ermG-containing strains.…”
mentioning
confidence: 95%
“…Lincomycin resistance in C. perfringens is relatively common, but it is usually conferred as MLS resistance by erm(B) or erm(Q) genes (10,11). Recent studies have shown that there has been an increase in lincomycin resistance in C. perfringens strains isolated from chickens in Belgium (28).…”
mentioning
confidence: 99%
“…Significantly, both determinants can be transferred into recipient cells by conjugation, although the processes are different (12,19,43). The pathogenic clostridia also carry other uncharacterized MLS resistance determinants and can potentially act as a source from which these resistance determinants may be transferred to other bacterial pathogens (10,18).…”
mentioning
confidence: 99%
“…Genes which hybridize to ermBP are also present in MLS-resistant isolates of Clostridium difficile and Clostridium paraputrificum (4). The second gene, ermQ, has been sequenced and shown to be the most common erythromycin resistance determinant in C. perfringens (3).…”
mentioning
confidence: 99%